2019
DOI: 10.3390/jcm8101530
|View full text |Cite
|
Sign up to set email alerts
|

General Anesthetic Agents and Renal Function after Nephrectomy

Abstract: The association between the choice of general anesthetic agents and the risk of acute kidney injury (AKI) and long-term renal dysfunction after nephrectomy has not yet been evaluated. We reviewed 1087 cases of partial or radical nephrectomy. The incidence of postoperative AKI, new-onset chronic kidney disease (CKD) and CKD upstaging were compared between general anesthetic agent groups (propofol, sevoflurane, and desflurane). Four different propensity score analyses were performed to minimize confounding for e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Several studies have compared the incidence of postoperative AKI between propofol and volatile anesthetic agents. In accordance with our results, some retrospective studies of nephrectomy, colorectal surgery, and major abdominal surgery demonstrated that propofol was associated with a reduced incidence of postoperative AKI [ 10 , 11 , 12 , 13 ]. In addition, patients treated with propofol had lower kidney specific biomarkers, pro-inflammatory cytokines, and incidences of postoperative AKI compared with those treated with sevoflurane during major abdominal or cardiac surgery [ 14 , 15 ].…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have compared the incidence of postoperative AKI between propofol and volatile anesthetic agents. In accordance with our results, some retrospective studies of nephrectomy, colorectal surgery, and major abdominal surgery demonstrated that propofol was associated with a reduced incidence of postoperative AKI [ 10 , 11 , 12 , 13 ]. In addition, patients treated with propofol had lower kidney specific biomarkers, pro-inflammatory cytokines, and incidences of postoperative AKI compared with those treated with sevoflurane during major abdominal or cardiac surgery [ 14 , 15 ].…”
Section: Discussionsupporting
confidence: 92%
“…A previous pilot study reported that remote ischemic conditioning reduced the incidence of AKI in patients undergoing partial nephrectomy [48]. Further studies are required to find modifiable risk factors of AKI or CKD progression after radical nephrectomy [9] and determinants for adaptive hyperfiltration in the contralateral kidney [39].…”
Section: Discussionmentioning
confidence: 99%
“…Demographic, baseline characteristics, and surgery-related data which were known to be associated with renal function after nephrectomy were obtained from our electronic medical records (Table 1) [1][2][3]9]. Serum creatinine values measured at 3, 12, 24, 36 months after surgery were collected.…”
Section: Patient Data and Outcome Measurementsmentioning
confidence: 99%
“…Moreover, a randomized trial demonstrated that sevoflurane reduced the release of cardiac troponin I significantly more than propofol did in patients with coronary artery disease undergoing vascular surgery [20]. However, considering the accumulating evidence indicating the lack of significant benefits of choosing volatile anesthetics over propofol during noncardiac surgery [16,21,[37][38][39], the 2014 ACC/AHA guidelines thus revised the recommendations regarding the choice of anesthetics for noncardiac surgery [26]. Subsequent randomized trials comparing TIVA with sevoflurane also reported no difference in their primary outcomes related to myocardial injury [22,40].…”
Section: Discussionmentioning
confidence: 99%
“…Volatile anesthetics have shown organ-protective effects, including that of the heart [11][12][13]. Propofol has anti-oxidant and anti-inflammatory actions; therefore, it has the potential to attenuate the ischemia-reperfusion injury of major organs [14][15][16]. Since cardiovascular complication after surgery involves sympathetic activation, hypercoagulability, arterial thrombosis, and inflammation [17][18][19], the choice of anesthetics has potential to affect the incidence of MACCE after noncardiac surgery in patients with a history of coronary stent insertion.…”
Section: Introductionmentioning
confidence: 99%